PENGARUH MATA PELAJARAN PENDIDIKAN PANCASILA TERHADAP CIVIC DISPOSITION SISWA DI SMK NEGERI 4 PEKANBARU - Bulan Angel Puspita; Supentri; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the problem of students who still do not have a good Civic Disposition and some problems of Civic Disposition are still found in SMK Negeri 4 Pekanbaru. In line with Ministerial Regulation No. 58 of 2014, attachment 1 states that Pancasila and Civic Education are general subjects of group A. With the aim of improving the knowledge, attitude competence, and skills of students who play a role as a force in community, national and state life. So that it can be realized that this Pancasila Education subject plays a role in the formation of character and character of students and actively participates in the learning process. The purpose of this study was to determine whether there is an influence of Pancasila education subjects on the Civic Disposition of class XI students at SMK Negeri 4 Pekanbaru. The population in this study were 575 class XI students at SMK Negeri 4 Pekanbaru, with a sample of 146 people. The data collection method used in this study was a closed questionnaire. Based on the data analysis in this study, there is a positive and significant influence between the influence of Pancasila education subjects on students' Civic Disposition, which shows that the value of ≥ 3,91 and a significant value of 0.000 ≤ 0.05. So it can be concluded that Ho is rejected and Ha is accepted, so that simultaneously Pancasila education (X) has a significant effect on the Civic Disposition (Y) of class XI students at SMK Negeri 4 Pekanbaru. The results of the analysis of the coefficient of determination test of the influence of Pancasila education (X) on Civic Disposition (Y) were 54%, while 46% was influenced by other variables not examined in this study.